2018
DOI: 10.3390/w10040347
|View full text |Cite
|
Sign up to set email alerts
|

Epibenthic Communities on Artificial Reefs in Greece, Mediterranean Sea

Abstract: The marine ecosystems in the Mediterranean are in alarming condition due to the complex and cumulative impacts of anthropogenic activities and natural disturbances. Management, conservation, and restoration of resources in these impacted ecosystems are among the priorities set by Mediterranean countries. Artificial reefs (ARs) are one of the countermeasures widely promoted. The present study describes the hard substrate epibenthic communities found on three ARs (Ierisssos, Kalymnos, and Preveza) located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This result contradicts the corresponding trend observed for sessile Polychaeta. Previous studies on Mediterranean ARs have shown both decreasing [7] and increasing trends [34,42] for motile Polychaeta abundance. The abundance of Crustacea has been substantially reduced since 2017 from about 14% to ca.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This result contradicts the corresponding trend observed for sessile Polychaeta. Previous studies on Mediterranean ARs have shown both decreasing [7] and increasing trends [34,42] for motile Polychaeta abundance. The abundance of Crustacea has been substantially reduced since 2017 from about 14% to ca.…”
Section: Discussionmentioning
confidence: 75%
“…In Greece, the first AR initiative was established in 1999 in the North Aegean Sea [4], and since then, several AR installation initiatives and studies have followed [1,3,5]. ARs are usually deployed to serve the protection, restoration, and enrichment of marine ecosystems by: (a) acting as nurseries for certain marine taxa, (b) increasing the heterogeneity and variety of the seabed, (c) facilitating recreational fisheries, (d) supporting aquaculture, (e) enhancing recreational diving spots, and (f) supporting experimental marine research [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation